A compilation of surface inherent optical properties and phytoplankton pigment concentrations from the Atlantic Meridional Transect - T. M. Jordan; G. Dall'Olmo; G. Tilstone; R. J. W. Brewin; F. Nencioli; R. Airs; C. S. Thomas; L. Schlüter (Earth System Science Data)
In situ measurements of particulate inherent optical properties (IOPs) – absorption (ap(λ)), scattering (bp(λ)), and beam attenuation (cp(λ)) – are crucial for the development of optical algorithms that retrieve biogeochemical quantities such as chlorophyll a, particulate organic carbon (POC), and total suspended matter (TSM). Here we present a compilation of particulate absorption–attenuation spectrophotometric data measured underway on nine Atlantic Meridional Transect (AMT) cruises between 50° N and 50° S from 2009–2019. The compilation includes coincident high-performance liquid chromatography (HPLC) phytoplankton pigment concentrations, which are used to calibrate transects of total chlorophyll a (Tot_Chl_a) concentrations derived from the ap(λ) line-height method. The IOP data are processed using a consistent methodology and include propagated uncertainties for each IOP variable, uncertainty quantification for the Tot_Chl_a concentrations based on HPLC match-ups, application of consistent quality-control filters, and standardization of output data fields and formats. The total IOP dataset consists of ∼310 000 measurements at a 1 min binning (∼270 000 hyper-spectral) and >700 coincident HPLC pigment surface samples (∼600 of which are coincident with hyper-spectral IOPs). We present the geographic variation in the IOPs, HPLC phytoplankton pigments, and ap-derived Tot_Chl_a concentrations which are shown to have uncertainties between 8 % and 20 %. Additionally, to stimulate further investigation of accessory pigment extraction from ap(λ), we quantify pigment correlation matrices and identify spectral characteristics of end-member ap(λ) spectra, where accessory pigment groupings are present in higher concentrations relative to Tot_Chl_a. All data are made publicly available in SeaBASS and NetCDF formats via the following links: https://seabass.gsfc.nasa.gov/archive/PML/AMT (Jordan et al., 2025a) and https://doi.org/10.5281/zenodo.12527954 (Jordan et al., 2024).